IMPLEMENTASI MODEL CTL BERBASIS PENDEKATAN ETNOMATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III DI UPT SDN 10 MAKALE - Idang, Rut; Salu Situru, Roberto; Salu, Benyamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the learning outcomes of third-grade students at UPT SDN 10 Makale through the implementation of the Contextual Teaching and Learning (CTL) model based on an ethnomathematics approach. The identified problem was the low learning outcomes in mathematics, caused by the lack of connection between the material and students' real-life experiences and local culture. The research method used was Classroom Action Research (CAR) with two cycles. Each cycle consisted of planning, implementation, observation, and reflection. Data were collected through observation, formative tests, interviews, and documentation. The results showed significant improvements in students' learning outcomes, both in terms of mathematical concept understanding and learning motivation. In the first cycle, 60% of students met the Minimum Competency Criteria (KKTP), while in the second cycle, the completion rate reached 85%. The application of the CTL model based on ethnomathematics had a positive impact on improving students' understanding of mathematical concepts by linking the material to local culture, particularly the Toraja carving motifs. This study recommends the implementation of similar models to enhance the quality of mathematics teaching in primary schools.